1965 Excavations of Amrit – 7th Season (Archives of Nassib Saliby) - al-Maqdissi, Michel; Ishaq, Eva (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2021)
A general introduction to the results of the field work at Amrith in 1965 (7th season) led by Nassib Saliby, through the presentation and study of unpublished documents preserved in the archive of the Syrian mission. These documents included the results of the archaeological excavations in the small tell located to the east of the temple, in addition to the archaeological sounding located on the northern side of the Favissa, and finally some another studies and basic soundings in the temple. The results of the excavations confirmed that the founding period of the tell dates back to the end of the 3rd millennium BC, and that the study focused on the great importance of the archaeological data discovered within the level of the Middle Bronze Age, as well as the architectural remains of an important building dating to the Late Phoenician Period (600-330 BC) in the sounding located north of Favissa.